2020
DOI: 10.1007/s42452-020-2521-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental study of cascade solar still

Abstract: In this study, a simulation was done to validate the experimental data of the new design of a cascade solar still, obtained from our existing prototype, for the climatic condition of Rabat, Morocco (34° 47′ N). The new design for the cascade solar still was developed using ANSYS FLUENT and modeled using FLUENT software. It has been found that the extracted data from the simulation's results are in good agreement with the experimental data. It was also examined that the productivity of the cascade solar still w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Mouhsin et al [37] suggested a cascade solar still design with a stepped structure of absorber plates. They applied solar radiation for CFD analysis of the still model and observed improved system efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…Mouhsin et al [37] suggested a cascade solar still design with a stepped structure of absorber plates. They applied solar radiation for CFD analysis of the still model and observed improved system efficiency.…”
Section: Related Workmentioning
confidence: 99%